INTEGRASI PRINSIP SUSTAINABLE DEVELOPMENT GOALS (SDGs) DALAM MANAJEMEN PENDIDIKAN ISLAM - Yusuf, M.; Hanif Satria Budi, M. (As-Sulthan Journal of Education, 2025)
Islamic education plays a strategic role in preparing a generation that is not only intellectually capable but also socially, spiritually, and ecologically sensitive. In the global context, the Sustainable Development Goals (SDGs) represent a shared agenda that requires the involvement of all sectors, including Islamic educational institutions. This article aims to examine the integration of SDG principles into Islamic education management, with an emphasis on the functions of planning, organizing, implementing, and supervising. The research method employed is library research with a descriptive-qualitative analysis, utilizing both primary and secondary literature related to SDGs and Islamic education management. The findings indicate that the principles of sustainability are essentially aligned with Islamic values, such as maqāṣid al-sharī‘ah and the human responsibility as khalīfah on earth. Such integration can be realized through environmentally based curricula, eco-friendly institutional governance, sustainable economic empowerment, and an academic culture that emphasizes social concern. Therefore, Islamic education management not only serves to produce high-achieving students but also acts as an agent of change toward a more just, prosperous, and sustainable society. This study is expected to contribute to the development of theory and practice in Islamic education management that is relevant to contemporary challenges while supporting the achievement of the SDGs.